Risk Factors for Hepatitis C Virus Transmission Obscure in Nigerian Patients - Olive Obienu; Sylvester Nwokediuko; Abraham Malu; Olufunmilayo A. Lesi (Gastroenterology Research and Practice)
Aim. To determine the prevalence of anti-HCV and risk factors associated with HCV infection in Nigerians. Materials and Method. Patients attending a general outpatient clinic were administered a structured questionnaire on the risk factors for HCV infection. They were also tested for anti-HCV using a third generation enzyme-linked immunosorbent assay. Result. The seroprevalence of anti-HCV was 4.7%. Among the risk factors evaluated, none was found to be significantly associated with anti-HCV seropositivity. Conclusion. The risk factors associated with HCV infection in Nigerian patients are obscure. This warrants further studies on the epidemiology of this important cause of liver disease.